2014
DOI: 10.1115/1.4027994
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Carbon Nanocapsule Particles as Lubricant Additive

Abstract: An experimental investigation is performed into the tribological properties of mineral oil lubricants containing carbon nanocapsules (CNCs) additives with various concentrations (wt.%). Friction characteristics and wear behaviors at contact interfaces are examined by the block-on-ring tests, high-resolution transmission electron microscopy (HRTEM), and mapping (MAP) analysis. The results suggest that the addition of CNCs to the mineral oil yields an effective reduction in the friction coefficient at the contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 54 publications
4
27
0
Order By: Relevance
“…This increase in friction coefficient with pressure has been also observed in previous NEMD simulations of hard nanoparticles [33] as well as in nanoscratching simulations of a-iron surfaces by diamond tips [42,43]. This relationship has also been observed experimentally for CNO additives [21,26]; however, other boundary friction experiments have shown increasing wear, but decreasing friction, with increasing pressure [23]. In these experiments, the decrease in friction with increasing pressure was evident both in the presence and in the absence of nanoparticles in a base oil [23].…”
Section: Effect Of Normal Pressuresupporting
confidence: 65%
See 1 more Smart Citation
“…This increase in friction coefficient with pressure has been also observed in previous NEMD simulations of hard nanoparticles [33] as well as in nanoscratching simulations of a-iron surfaces by diamond tips [42,43]. This relationship has also been observed experimentally for CNO additives [21,26]; however, other boundary friction experiments have shown increasing wear, but decreasing friction, with increasing pressure [23]. In these experiments, the decrease in friction with increasing pressure was evident both in the presence and in the absence of nanoparticles in a base oil [23].…”
Section: Effect Of Normal Pressuresupporting
confidence: 65%
“…Both CND [9,[12][13][14][15][16][17] and CNO [18][19][20][21][22][23][24][25][26] have been shown to significantly reduce friction and wear of steel surfaces under boundary lubrication conditions. Specifically, CNO has been shown to reduce the friction coefficient by &85 % when used as a solid lubricant [22].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the dispersion property of the CNC in the mineral oil, the CNC particles were surface modified with alkyl chains and wet–mechanical ground to reduce the surface energy [ 85 ]. It was proved by researchers that sheet-like ZnO@graphene nanoparticles were more suitable for dynamic friction environments in ester base oil while local agglomeration could be seen in the prism-like nanoparticles, as can be seen in Figure 13 [ 86 ], which meant that the morphologies of the particles could also affect the dispersion properties.…”
Section: Applicationsmentioning
confidence: 99%
“…However, chemically synthesizing GO nanoparticles involves a long and complex procedure [ 29 ]. In comparison, carbon nanocapsules (CNCs), with a more cost-effective and scalable synthesis process, are regarded to be a more attractive option for tribological applications [ 30 , 31 ]. In a previous study [ 30 ], we added CNCs with various concentrations to mineral oil lubricant and evaluated the friction characteristics and wear behavior at the contact interface using block-on-ring tests.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, carbon nanocapsules (CNCs), with a more cost-effective and scalable synthesis process, are regarded to be a more attractive option for tribological applications [ 30 , 31 ]. In a previous study [ 30 ], we added CNCs with various concentrations to mineral oil lubricant and evaluated the friction characteristics and wear behavior at the contact interface using block-on-ring tests. The results showed that CNCs led to a significant reduction in the COF at the contact surface due to their structural evolution under the effects of the contact force.…”
Section: Introductionmentioning
confidence: 99%